2022
DOI: 10.1007/s12015-022-10439-4
|View full text |Cite
|
Sign up to set email alerts
|

Outgrowth Endothelial Cell Conditioned Medium Negates TNF-α-Evoked Cerebral Barrier Damage: A Reverse Translational Research to Explore Mechanisms

Abstract: Improved understanding of the key mechanisms underlying cerebral ischemic injury is essential for the discovery of efficacious novel therapeutics for stroke. Through detailed analysis of plasma samples obtained from a large number of healthy volunteers (n = 90) and ischemic stroke patients (n = 81), the current study found significant elevations in the levels of TNF-α at baseline (within the first 48 h of stroke) and on days 7, 30, 90 after ischaemic stroke. It then assessed the impact of this inflammatory cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…Biochemical analyses of HV and IS patient plasma samples revealed consistent increases in pro-inflammatory cytokine, TNF-α in IS patients. This confirmed a shift to pro-inflammatory state after stroke [ 27 , 28 ]. However, increased availability of pro-angiogenic cytokine, VEGF and the diminished availability of anti-angiogenic factors that normally inhibit the activity of VEGF i.e.…”
Section: Discussionsupporting
confidence: 62%
“…Biochemical analyses of HV and IS patient plasma samples revealed consistent increases in pro-inflammatory cytokine, TNF-α in IS patients. This confirmed a shift to pro-inflammatory state after stroke [ 27 , 28 ]. However, increased availability of pro-angiogenic cytokine, VEGF and the diminished availability of anti-angiogenic factors that normally inhibit the activity of VEGF i.e.…”
Section: Discussionsupporting
confidence: 62%
“…The exogenous addition of EPCs repairs the integrity of an in vitro BBB model under OGD conditions and attenuates ischaemia-evoked oxidative stress and the apoptosis of endothelial cells [77,85,86]. Besides administering the stem cells directly, the condition media of outgrowth endothelial cells were found to negate the deleterious effects of TNF-α on BBB function in an in vitro triculture model of the BBB [87]. EPCs are able to secret a wide range of substances to regulate angiogenesis, migration, proliferation, and antipoptosis, including angiogenin, HGF, PDGF, VEGF, and PBEF [88].…”
Section: Endothelial Progenitor Cells (Epcs)mentioning
confidence: 99%
“…EPCs are able to secret a wide range of substances to regulate angiogenesis, migration, proliferation, and antipoptosis, including angiogenin, HGF, PDGF, VEGF, and PBEF [88]. A clinical study indicated that post-stroke patients have elevated levels of TNF-α, and an in vitro study determined that TNF-α significantly impairs the function and integrity of the BBB [87,89]. Aside from their therapeutic potential, EPCs can also be used as diagnostic and prognostic biomarkers.…”
Section: Endothelial Progenitor Cells (Epcs)mentioning
confidence: 99%
“…An exogenous addition of OECs to an in vitro model of the BBB (established with astrocytes, pericytes and BMECs) repaired the wound scratch-induced on a layer of BMECs in serum-free conditions [ 63 ]. Additionally, a very recent study demonstrated that an outgrowth endothelial cell-derived conditioned media (OEC-CM) prevents the damaging effects of TNF-α on the BBB since the levels of TNF-α were found to be significantly elevated on days 2, 7, 30 and 90 after ischemic stroke and TNF-α impairs function and integrity of the BBB, which is the main early cause of death after IS [ 64 ].…”
Section: Ischemic Strokementioning
confidence: 99%